Communication and ‘revolt’ - Bert Olivier (Communicare)
‘Revolt’ is usually associated with ‘rebellion’, or ‘revolution’ in a political sense, and at an intuitive level there is certainly a connection or similarity among these three concepts. The psychoanalytical theorist and philosopher, Julia Kristeva, has however developed a notion of ‘revolt’ (and, related to it, of ‘revolution’) that goes far beyond the common understanding of the term. Moreover, in her understanding of the concept, ‘revolt’ may indeed be a ‘communicational’ prerequisite for contemporary ‘globalised’ society to break out of an invidious (and potentially violent) standoff between a dominant world culture, subject to the logic of the market, on the one hand, and a fundamentalist ideological reaction to it, on the other. Kristeva points the way to a creative enlivening of individuals’ lives, as well as of society at large, through her passionate elaboration on the potential for ‘revolution’ in language and communication, and also her development of the notion of ‘revolt’ as a legacy of Western culture – a legacy which is under threat in the present ‘culture of the spectacle’.